Monoclonal antibodies in the management of asthma: Dead ends, current status and future perspectives - Kardas, Grzegorz; Panek, Michał; Kuna, Piotr; Damiański, Piotr; Kupczyk, Maciej (Frontiers in Immunology, 2022)
Patients with moderate-to-severe asthma may now be treated using a variety of monoclonal antibodies that target key inflammatory cytokines involved in disease pathogenesis. Existing clinical data on anti-IgE, anti-IL-5 and other immunological pathways indicate these therapies to offer reduced exacerbation rates, improved lung function, greater asthma control and better quality of life. However, as several patients still do not achieve satisfactory clinical response with the antibodies available, many more biologics, aiming different immunological pathways, are under evaluation. This review summarizes recent data on existing and potential monoclonal antibodies in asthma. Recent advances have resulted in the registration of a new antibody targeting TSLP (tezepelumab), with others being under development. Some of the researched monoclonal antibodies (e.g. anti-IL-13 tralokinumab and lebrikizumab or anti-IL-17A secuinumab) have shown optimistic results in preliminary research; however, these have been discontinued in asthma clinical research. In addition, as available monoclonal antibody treatments have shown little benefit among patients with T2-low asthma, research continues in this area, with several antibodies in development. This article summarizes the available pre-clinical and clinical data on new and emerging drugs for treating severe asthma, discusses discontinued treatments and outlines future directions in this area.